Cost trend analysis of initial cancer treatment in Taiwan. - Tsai-Yun Li (Public Library of Science (PLoS), 2014)
Background Despite the high cost of initial cancer care, that is, care in the first year after diagnosis, limited information is available for specific categories of cancer-related costs, especially costs for specific services. This study purposed to identify causes of change in cancer treatment costs over time and to perform trend analyses of the percentage of cancer patients who had received a specific treatment type and the mean cost of care for patients who had received that treatment. Methodology/principal findings The analysis of trends in initial treatment costs focused on cancer-related surgery, chemotherapy, radiation therapy, and treatments other than active treatments. For each cancer-specific trend, slopes were calculated for regression models with 95% confidence intervals. Analyses of patients diagnosed in 2007 showed that the National Health Insurance (NHI) system paid, on average, $10,780 for initial care of a gastric cancer patient and $10,681 for initial care of a lung cancer patient, which were inflation-adjusted increases of $6,234 and $5,522, respectively, over the 1996 care costs. During the same interval, the mean NHI payment for initial care for the five specific cancers increased significantly (p<0.05). Hospitalization costs comprised the largest portion of payments for all cancers. During 1996-2007, the use of chemotherapy and radiation therapy significantly increased in all cancer types (p<0.05). In 2007, NHI payments for initial care for these five cancers exceeded $12 billion, and gastric and lung cancers accounted for the largest share. Conclusions/significance In addition to the growing number of NHI beneficiaries with cancer, treatment costs and the percentage of patients who undergo treatment are growing. Therefore, the NHI must accurately predict the economic burden of new chemotherapy agents and radiation therapies and may need to develop programs for stratifying patients according to their potential benefit from these expensive treatments.